(untitled) - Lala, Parag K. (Hoboken, N.J., 2007)
A major objective of this book is to fill the gap between traditional logic design principles and logic design/optimization techniques used in practice. Over the last two decades several techniques for computer-aided design and optimization of logic circuits have been developed. However, underlying theories of these techniques are inadequately covered or not covered at all in undergraduate text books. This book covers not only the "classical" material found in current text books but also selected materials that modern logic designers need to be familiar with.
Keywords: Logic design,Logic circuits,Digital electronics,Thiết kế Logic,Logic mạch,Rhiết bị điện tử kỹ thuật số.; Design and construction,Thiết kế và xây dựng